Tuscan and Genoese Aspirations to Transoceanic Trade (17th Century) - Tosco, Giorgio (Early Modern History and Modern History E-Books Online, Collection 2025., 2026)
Many small, early modern European states tried to follow in the footsteps of their bigger neighbours and expand beyond the oceans. Tuscan and Genoese Aspirations to Transoceanic Trade (17th Century) traces the little-known history of two of these states: the Grand Duchy of Tuscany and the Republic of Genoa. These two old and prestigious commercial centres found themselves gradually displaced over the 17th century as the centre of gravity of the European economy moved away from the Mediterranean. In an attempt to combat this, Florentine and Genoese elites collected information and reviewed projects, established joint-stock companies, and sent ships to East Asia and the Americas. While their plans failed, their vicissitudes illustrate the mechanisms that stood behind European expansion overseas, and how its results differed widely from expectations.